Genome‐Wide Allelic Methylation Analysis Reveals Disease‐Specific Susceptibility to Multiple Methylation Defects in Imprinting Syndromes. Issue 4 (19th February 2013) - Court, Franck; Martin‐Trujillo, Alex; Romanelli, Valeria; Garin, Intza; Iglesias‐Platas, Isabel; Salafsky, Ira; Guitart, Miriam; Perez de Nanclares, Guiomar; Lapunzina, Pablo; Monk, David
<x xml:space="preserve">Abstract</x> Genomic imprinting is the parent‐of‐origin specific allelic transcriptional silencing observed in mammals. Abnormal methylation at imprinted loci is associated with various imprinting syndromes. We analysed of 26 imprinted DMRs and identified multi‐locus hypomethyaltion in numerous BWS, TNDM and PHP‐1B patients, and an individual with SRS, but not in PWS or AS patients. A mutation screen of ZFP57, NLRP2, NLRP7 and KHDC3L revealed only one causative change, a ZFP57 1bp deletion, in a TNDM patient with multiple‐hypomethylation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>